The Effect Was Purple Sweet Potato Flour On The Quality Of Dried Sus - Wulandari, Laila Fauziah; Elida, Elida (Universitas Negeri Padang, 2021)
This research was motivated by the lack of utilization of local food ingredients such as purple sweet potato flour in processed food; one of them was dried sus. The purple sweet potato flour was used to reduce the dependence on wheat and as an effort to increase food endurance. This study aimed to analyze the effect of purple sweet potato flour substitution as much as 10%, 20%, and 30% on the dried sus quality which included external quality (volume, shape, color) and internal quality (aroma, texture, taste). This type of research was a pure experiment with a completely randomized design method. The data used was primary data obtained through an organoleptic test by 5 expert panelists. The data analysis of this study used ANOVA test.If Fcount > Ftable, so that it will be continued with Duncan's Test. The result showed that there was no influenceon external quality (volume and shape). While on the external quality of color there was a significant effect, so that is was continued the Duncan Test. On the internal quality (aroma and taste of purple sweet potato) showed a significant effect, so that it wascontinued the Duncan Test. Internal quality research result (texture and savory taste)showed there was no significant effect.